2023
DOI: 10.7150/ijms.80220
|View full text |Cite
|
Sign up to set email alerts
|

Klotho promotes AMPK activity and maintains renal vascular integrity by regulating the YAP signaling pathway

Abstract: The development and formation of mammalian blood vessels are closely related to the regulation of signal transduction pathways. Klotho/AMPK and YAP/TAZ signaling pathways are closely related to angiogenesis, but the internal relationship between them is not clear. In this study, we found that Klotho heterozygous deletion mice (Klotho +/- mice) had obvious thickening of the renal vascular wall, obvious enlargement of vascular volume, and significant proliferation and pricking of vascular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
2
3
0
Order By: Relevance
“…LATS1 is a core and upstream component of the Hippo pathway, which can regulate the downstream effectors, YAP1 and TAZ. 40 These observations support the hypothesis that AMPK might serve as an essential factor in the regulatory effect of HG on YAP1/TAZ function. in cancer cell autophagy and metabolism, a deeper investigation into these other pathways is needed.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…LATS1 is a core and upstream component of the Hippo pathway, which can regulate the downstream effectors, YAP1 and TAZ. 40 These observations support the hypothesis that AMPK might serve as an essential factor in the regulatory effect of HG on YAP1/TAZ function. in cancer cell autophagy and metabolism, a deeper investigation into these other pathways is needed.…”
Section: Discussionsupporting
confidence: 74%
“…In mouse renal vascular endothelial cells, large tumour suppressor 1 (LATS1) expression and p‐LATS1 interaction with the AMPK protein decreased significantly. LATS1 is a core and upstream component of the Hippo pathway, which can regulate the downstream effectors, YAP1 and TAZ 40 . These observations support the hypothesis that AMPK might serve as an essential factor in the regulatory effect of HG on YAP1/TAZ function.…”
Section: Discussionsupporting
confidence: 74%
“…The mechanism involves the activation of AMPK, the downstream increase of SCRIB (Liu et al, 2020 ), Angiomiotin-like protein 1 and 2 (AMOTL1/2) and Angiomotin (AMOT) (DeRan et al, 2014 ) protein levels, which are involved in LATS1/2 stabilization and therefore AMPK-dependent YAP degradation. Furthermore, another study showed that Klotho ± mice, a widely used knockout mouse model in aging research that displays extremely short life span and premature aging (Kuro-o et al, 1997 ) display a weaker AMPK-LATS1 interaction as well as decreased AMPK-dependent phosphorylation of YAP (Luo et al, 2023 ). Although the exact mechanism has not been described yet, these data suggest that there is a direct interaction between AMPK and LATS1 which might be facilitated by the anti-aging protein Klotho.…”
Section: Nutrient Signalingmentioning
confidence: 99%
“…Currently, it is known that klotho and FGF21 proteins can affect several signaling pathways although it seems that the inhibition of TGF-β signaling might be involved in tissue fibrosis (Ding et al 2019 ; Wang et al 2023a , b ). There are several investigations indicating that both the klotho and FGF21 proteins are able to activate AMPK signaling in many experimental models (Salminen et al 2017b ; Luo et al 2023 ). For instance, Luo et al ( 2023 ) demonstrated that the klotho protein stimulated AMPK signaling which subsequently promoted the phosphorylation and degradation of the YAP protein in mouse kidney.…”
Section: Does Ampk Signaling Alleviate the Aging Process By Inhibitin...mentioning
confidence: 99%
“…There are several investigations indicating that both the klotho and FGF21 proteins are able to activate AMPK signaling in many experimental models (Salminen et al 2017b ; Luo et al 2023 ). For instance, Luo et al ( 2023 ) demonstrated that the klotho protein stimulated AMPK signaling which subsequently promoted the phosphorylation and degradation of the YAP protein in mouse kidney. As described above, YAP/TAZ signaling is recognized as an important fibrogenic pathway.…”
Section: Does Ampk Signaling Alleviate the Aging Process By Inhibitin...mentioning
confidence: 99%